2016
DOI: 10.1002/14651858.cd011108.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Hydromorphone for cancer pain

Abstract: This review indicated little difference between hydromorphone and other opioids in terms of analgesic efficacy. Data gathered in this review showed that hydromorphone had a similar effect on participant-reported pain intensity as reported for oxycodone and morphine. Participants generally achieved no worse than mild pain after taking hydromorphone, which is comparable with the other drugs. It produced a consistent analgesic effect through the night and could be considered for use in people with cancer pain exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…16 A Cochrane review concluded that hydromorphone has an analgesic efficacy that is similar to morphine and oxycodone in cancer patients. 14 There are limited studies regarding opioid conversions and rotations involving IV hydromorphone. Although the conversion ratio (CR) of IV morphine to oral morphine is well established, 6,17 the same is not true for hydromorphone.…”
Section: Introductionmentioning
confidence: 99%
“…16 A Cochrane review concluded that hydromorphone has an analgesic efficacy that is similar to morphine and oxycodone in cancer patients. 14 There are limited studies regarding opioid conversions and rotations involving IV hydromorphone. Although the conversion ratio (CR) of IV morphine to oral morphine is well established, 6,17 the same is not true for hydromorphone.…”
Section: Introductionmentioning
confidence: 99%
“…Although opioids such as morphine are used for the treatment of advanced bone cancer pain, an increasing dose of morphine is required . Given that the side effects caused by a higher dose of morphine, the development of a novel strategy to enhance the analgesic effects of morphine to control bone cancer pain and further to reduce its side effects also becomes an important issue for treatment and management of patients with advanced bone cancer …”
mentioning
confidence: 99%
“…5 Given that the side effects caused by a higher dose of morphine, the development of a novel strategy to enhance the analgesic effects of morphine to control bone cancer pain and further to reduce its side effects also becomes an important issue for treatment and management of patients with advanced bone cancer. [6][7][8] To study bone cancer-induced pain, a rat model has been commonly used. 9,10 Rat mammary gland carcinoma cells (i.e., breast sarcocarcinoma Walker 256 cells) are implanted into the tibia bone cavity and this can develop significant mechanical and thermal hyperalgesia.…”
mentioning
confidence: 99%
“…The latest review involved 604 patients from four trials that compared hydromorphone to oxycodone or morphine. Similar analgesic efficacy was demonstrated between groups with both comparisons ( level of evidence II, degree of recommendation A ) [ 27 ].…”
Section: First and Second Stepmentioning
confidence: 53%